Legal Protection For Children After Divorce Through The Decision Of The Religious Court Of Medan City (Analysis Of Child Protection Law No. 23 Of 2002) - Nur'aini; Khair, Nispul; Harahap, Yadi (The Islamic Education and Multiculturalism Foundation, 2024)
This study aims to analyze in depth the protection of children after divorce through the decision of the Medan City Religious Court according to Law No. 23 of 2002. This type of research is a qualitative empirical study with a case study approach, laws and regulations in the KHI and conceptually. The data collection methods used are interviews, observations, and documentation. The subject of the study was the head of the Medan City Religious Court. The results of the study describe that (1) The regulation of legal protection for children after divorce in the Medan City Religious Court is based on seven legal bases as rules in deciding child custody cases in the Medan City Religious Court, (2) The application of the law to child custody after divorce in the Medan City Religious Court is in accordance with Law No. 23 of 2002 concerning child protection even though there are several obstacles and barriers. The solution to overcome all of this is the need for re-socialization of the application of Law No. 23 of 2002, (3) The judge's considerations in deciding child custody after divorce in the Medan City Religious Court are based on the principles of justice, legal certainty and a problematic, social, psychological approach in order to achieve a decision that satisfies both parties.